Carbon Nano-onions: Potassium Intercalation and Reductive Covalent Functionalization - Perez-Ojeda Rodriguez, Maria Eugenia; Castro, Edison; Kröckel, Claudia; Lucherelli, Matteo Andrea; Ludacka, Ursula; Kotakoski, Jani; Werbach, Katharina; Peterlik, Herwig; Melle-Franco, Manuel; Chacón-Torres, Julio C.; Hauke, Frank; Echegoyen, Luis; et al. (Journal of the American Chemical Society, 2021)
Herein we report the synthesis of covalently functionalized carbon nano-onions (CNOs) via a reductive approach using unprecedented alkali-metal CNO intercalation compounds. For the first time, an in situ Raman study of the controlled intercalation process with potassium has been carried out revealing a Fano resonance in highly doped CNOs. The intercalation was further confirmed by electron energy loss spectroscopy and X-ray diffraction. Moreover, the experimental results have been rationalized with DFT calculations. Covalently functionalized CNO derivatives were synthesized by using phenyl iodide and n-hexyl iodide as electrophiles in model nucleophilic substitution reactions. The functionalized CNOs were exhaustively characterized by statistical Raman spectroscopy, thermogravimetric analysis coupled with gas chromatography and mass spectrometry, dynamic light scattering, UV–vis, and ATR-FTIR spectroscopies. This work provides important insights into the understanding of the basic principles of reductive CNOs functionalization and will pave the way for the use of CNOs in a wide range of potential applications, such as energy storage, photovoltaics, or molecular electronic

Structural stability in potassium doped single-walled carbon nanotubes, and surface functionalization - Kröckel, Claudia; Ludacka, Ursula; Singh, Rajendra; Kotakoski, Jani; Hauke, Frank; Hirsch, Andreas; Reich, Stephanie; Chacón-Torres, Julio C. (Carbon, 2025)
A systematic investigation of potassium intercalated HiPCO-enriched single walled carbon nanotubes (SWCNT) was conducted, with a focus on the material's structural stability after doping and exposure to ambient conditions for 12 months. Three unprecedented aspects have been revealed: i) Semiconducting nanotubes retain the charge transferred from K as predicted for graphite intercalation compounds. Both species, metallic and semiconducting, exhibit charge stabilization for over a week exposed to air. ii) After exposure to air and harsh chemical reaction conditions, the individualized potassium doped SWCNT showed an intact hexagonal lattice, which demonstrated high structural stability. iii) During exposure to air, functionalization sites appeared on the surface of the n-type doped nanotubes, but there was no significant structural damage observed. We confirm that SWCNT species have a high structural stability in diameters above 0.75 nm explained as an adapting process of the electronic structure from the carbon nanotubes towards a high electron doping followed by a remarkable crystalline defect-free tubular structure. This information is highly relevant for the carbon community revealing for the first time the stability of SWCNT after being highly doped and exposed to air. This work highlights for potential applications of SWCNT in the development of bright photoluminescence nanotubes that strongly depend on their structure, defect content, size, and metallicity.
CRIS-Team Scopus Importer:2025-01-31
Keywords: HiPCO enriched SWCNT; n-type doping; Raman spectroscopy; Surface functionalization; Transmission electron microscopy

Supramolecular interactions in graphene–chitosan composites with plasmonic nanoparticles - Briceño, Sarah; Layana, Lorena; Berrezueta-Palacios, Charlotte; Guerrero-León, Lenin Andres; Kröckel, Claudia; Mowbray, Duncan John; Chacón-Torres, Julio C. (Carbon Trends, 2024)
The supramolecular interactions between graphene and biopolymers, such as chitosan, determine both whether nanostructured-hybrid materials are formed and their technologically relevant physical/chemical properties. However, there is still a fundamental lack of knowledge about how nanocomposites based on chitosan and graphene are formed, as well as their intrinsic structure and interaction with plasmonic nanoparticles. In this work, we provide an in-depth understanding of the supramolecular interactions between chitosan and graphene in the formation of graphene–chitosan nanocomposites with gold or silver nanoparticles. To do so, we employ a combination of Raman spectroscopy, Fourier-transformed infrared (FTIR) spectroscopy, atomic force microscopy (AFM), scanning electron microscopy (SEM), and X-ray photoelectron spectroscopy (XPS) measurements with density functional theory (DFT) calculations to reveal the mechanism and driving forces behind these supramolecular interactions between graphene and chitosan. Specifically, we show they are based on a charge transfer process derived from the protonation of the amine groups of chitosan in acidic media. The understanding of the supramolecular interaction between graphene and chitosan that we provide herein should prove of great importance and interest to the material sciences and biomedical engineering fields.
CRIS-Team Scopus Importer:2024-10-25
Keywords: Biopolymers; Chitosan; DFT; FTIR; Graphene; Nanocomposite; Plasmonic nanoparticles; Raman spectroscopy

Understanding the Electron-Doping Mechanism in Potassium-Intercalated Single-Walled Carbon Nanotubes - Kröckel, Claudia; Preciado-Rivas, María Rosa; Torres-Sánchez, Victor Alexander; Mowbray, Duncan J.; Reich, Stephanie; Hauke, Frank; Chacón-Torres, Julio C.; Hirsch, Andreas (Journal of the American Chemical Society, 2020)
Single-walled carbon nanotubes (SWCNTs) can be doped with potassium, similar to graphite, leading to intercalation compounds. These binary systems exhibit a clear metallic character. However, the entire picture of how electron doping (e-doping) modifies the SWCNTs' vibrational spectra as a function of their diameter, chirality, and metallicity is still elusive. Herein, we present a detailed study of the intercalation and solid state reduction of metallic and semiconducting enriched HiPco SWCNTs. We performed a combined experimental and theoretical study of the evolution of their Raman response with potassium exposure, focusing specifically on their radial breathing mode (RBM). We found the charge donated from the potassium atoms occupies antibonding π orbitals of the SWCNTs, weakening their C-C bonds, and reducing the RBM frequency. This RBM downshift with increasing doping level is quasi-linear with a steplike behavior when the Fermi level crosses a van Hove singularity for semiconducting species. Moreover, this weakening of the C-C bonds is greater with decreasing curvature, or increasing diameter. Overall, this suggests the RBM downshift with e-doping is proportional to both the SWCNT's integrated density of states (DOS) ϱ(ε) and diameter d. We have provided a precise and complete description of the complex electron doping mechanism in SWCNTs up to a charge density of -18 me/C, far beyond that achievable by standard gate voltage studies, not being the highest doping possible, but high enough to track the effects of doping in SWCNTs based on their excitation energy, diameter, band gap energy, chiral angle, and metallicity. This work is highly relevant to tuning the electronic properties of SWCNTs for applications in nanoelectronics, plasmonics, and thermoelectricity.
CRIS-Team Scopus Importer:2020-02-14

UNIQUE EXTRA-LONG CHEMICALLY-DERIVED GRAPHITIC PYRAMIDAL RIBBONS - Chacón-Torres, Julio C.; Andrade-Guevara, Denise; García-Betancourt, María Luisa; Kröckel, Claudia (Acta Microscopica, 2024)
In this letter, unique extra-long chemically derived pyramidal graphitic ribbons (PGR) were individualized and deposited onto a SiO2 substrate via simple spin-coating. The length of the individualized PGRs was found to exceed the average length of graphene nanoribbons (GNRs) by hundreds of microns. The physicochemical individualization method resulted in the creation of a novel “graphene nanoribbon intercalation compound” (GNRIC), following a strict stoichiometric relation between the GNR powder and alkali metals. Our experiments were conducted with the use of Na and K as intercalants at NaC8, KC8, and KC24 concentrations. Furthermore, we exposed them to THF and discovered that the nanoribbon bundles obtained from CVD bottom-up bulk synthesis of GNRs can be exfoliated. The exfoliated nanoribbons (ex-GNRs) were analyzed using SEM, Raman spectroscopy, optical microscopy, and AFM, revealing the existence of ribbon-like pyramidal nanostructures that are larger than 100 µm. The morphology of these graphitic ribbons, brings a new starting point and immense potential to the development of graphene-based devices for optoelectronics and solar cells.
CRIS-Team Scopus Importer:2024-07-05
Keywords: Atomic force microscopy; Individualization; Intercalation compounds; Pyramidal graphitic ribbons; Raman spectroscopy